Low Oleic Acid-Derived Repression of Jasmonic Acid-Inducible Defense Responses Requires the WRKY50 and WRKY51 Proteins(1)([W])([OA]) - Gao, Qing-Ming (American Society of Plant Biologists, 2011)
Signaling induced upon a reduction in oleic acid (18:1) levels simultaneously up-regulates salicylic acid (SA)-mediated responses and inhibits jasmonic acid (JA)-inducible defenses, resulting in enhanced resistance to biotrophs but increased susceptibility to necrotrophs. SA and the signaling component Enhanced Disease Susceptibility1 function redundantly in this low-18:1-derived pathway to induce SA signaling but do not function in the repression of JA responses. We show that repression of JA-mediated signaling under low-18:1 conditions is mediated via the WRKY50 and WRKY51 proteins. Knockout mutations in WRKY50 and WRKY51 lowered SA levels but did not restore pathogenesis-related gene expression or pathogen resistance to basal levels in the low-18:1-containing Arabidopsis (Arabidopsis thaliana) mutant, suppressor of SA insensitivity2 (ssi2). In contrast, both JA-inducible PDF1.2 (defensin) expression and basal resistance to Botrytis cinerea were restored. Simultaneous mutations in both WRKY genes (ssi2 wrky50 wrky51) did not further enhance the JA or Botrytis-related responses. The ssi2 wrky50 and ssi2 wrky51 plants contained high levels of reactive oxygen species and exhibited enhanced cell death, the same as ssi2 plants. This suggested that high reactive oxygen species levels or increased cell death were not responsible for the enhanced susceptibility of ssi2 plants to B. cinerea. Exogenous SA inhibited JA-inducible PDF1.2 expression in the wild type but not in wrky50 or wrky51 mutant plants. These results show that the WRKY50 and WRKY51 proteins mediate both SA- and low-18:1-dependent repression of JA signaling.